The Development Lectora Inspire Based Learning Media for High School Students in Learning History - Budi Purnomo (Indonesian Research Journal in Education |IRJE|, 2021)
This research aimed to develop Lectora Inspire App for history learning in high schools. Purposely, the stages of the development in using the ADDIE model which include the steps of analysis, design, development, implementation, and evaluation. Interview and questionnaires were administered in order to collect data. The interview data were analyzed qualitatively while the questionnaires were analyzed quantitatively. There were 35 respondents from one of the high schools in Jambi who were grouped into three groups, namely 3 students for a small individual group, 10 students for a small group, and 22 students for a large group. The results of this development research revealed that Lectora Inspire App based on history learning was valid based on the assessment of material experts and media experts. Moreover, based on the results of small group trials, limited group trials, and large group trials,it showed that Lectora Inspire App were effective as history learning media. Recommendations are also discussed for future research and practices.